Anti-CD163-dexamethasone protects against apoptosis after ischemia/reperfusion injuries in the rat liver. Issue 4 (December 2015) - Møller, Lin Nanna Okholm; Knudsen, Anders Riegels; Andersen, Kasper Jarlhelt; Nyengaard, Jens Randel; Hamilton-Dutoit, Stephen; Okholm Møller, Elise Marie; Svendsen, Pia; Møller, Holger Jon; Moestrup, Søren Kragh; Graversen, Jonas Heilskov; Mortensen, Frank Viborg
Abstract: Aim: The Pringle maneuver is a way to reduce blood loss during liver surgery. However, this may result in ischemia/reperfusion injury in the development of which Kupffer cells play a central role. Corticosteroids are known to have anti-inflammatory effects. Our aim was to investigate whether a conjugate of dexamethasone and antibody against the CD163 macrophage cell surface receptor could reduce ischemia/reperfusion injury in the rat liver. Methods: Thirty-six male Wistar rats were used for the experiments. Animals were randomly divided into four groups of eight receiving anti-CD163-dexamethasone, high dose dexamethasone, low dose dexamethasone or placebo intravenously 18 h before laparotomy with subsequent 60 min of liver ischemia. After reperfusion for 24 h the animals had their liver removed. Bloods were drawn 30 min and 24 h post ischemia induction. Liver cell apoptosis and necrosis were analyzed by stereological quantification. Results: After 24 h' reperfusion, the fraction of cell in non-necrotic tissues exhibiting apoptotic profiles was significantly lower in the high dose dexamethasone (p = 0.03) and anti-CD163-dex (p = 0.03) groups compared with the low dose dexamethasone and placebo groups. There was no difference in necrotic cell volume between groups. After 30 min of reperfusion, levels of haptoglobin were significantly higher in the anti-CD163-dex and high dose dexamethasone groups. Alanine aminotransferase and alkaline phosphatase were significantly higher in the high dose dexamethasone group compared to controls after 24 h' reperfusion. Conclusions: We show that pharmacological preconditioning with anti-CD163-dex and high dose dexamethasone reduces the number of apoptotic cells following ischemia/reperfusion injury. Highlights: We investigated the effect of pharmacologic preconditioning with HDD, LDD and anti-CD163-dex on ischemia/reperfusion injury. Liver cell apoptosis and necrosis were analyzed by stereological quantification. Anti-CD163-dex and high dose dexamethasone reduces the number of apoptotic cells following ischemia/reperfusion injury.